Seni Tradisi Memupuk Jatidiri Bangsa (Suatu Harapan) - Hartoyo Soehari (Gemawisata: Jurnal Ilmiah Pariwisata, 2020)
A person's identity can be interpreted as the basic nature, mentality, character, or self-esteem of the person. The character of the Indonesian people is to live a simple life, obey the rules, and like to work together. Gotong royong is a harmonious cooperation that produces products that are beneficial to people's lives. For example gamelan, various types of gamelan instruments are beaten together to produce harmonious musical sounds that are pleasant to hear, useful, and make people relaxed and not stressed.